Composite nanofibers by coating polypyrrole on the surface of polyaniline nanofibers formed in presence of phenylenediamine as electrode materials in neutral electrolyte. (20th July 2017) - Li, Tao; Zhou, Yi; Dou, Zhenjun; Ding, Lei; Dong, Shu; Liu, Na; Qin, Zongyi
Graphical abstract: Highlights: Obtaining polyaniline nanofibers in the presence of o–phenylenediamine (oPA), m–phenylenediamine (mPA) and p–phenylenediamine (pPA), respectively. Coating polypyrrole on the surface of pre–prepared polyaniline nanofibers. Exhibiting enhanced electrochemical performance of composite nanofibers in neutral electrolyte. Abstract: Polyaniline/Polypyrrole (PANi/PPy) composite nanofibers with core–shell structures were prepared by covering PPy thin layers on the surface of PANi nanofibers as high–performance electrode materials for supercapacitors in neutral aqueous electrolyte. Core part of PANi was firstly synthesized through chemical oxidative polymerization of aniline monomers in the presence of phenylenediamine (PDA) isomers including o–phenylenediamine (o–PDA), m–phenylenediamine (m–PDA) and p–phenylenediamine (p–PDA) without the assistance of any templates or usage of organic solvents, and then the shell part of PPy was fabricated by in–site chemical oxidative polymerization of pyrrole with the above–mentioned PANi as a seed. PANis and corresponding composite were investigated by field–emission scanning electron microscopy, ultraviolet–visible spectroscopy, Fourier transform infrared and Raman spectrometry, and wide angle X–ray diffractometer. Furthermore, electrochemical behaviors of PANis in H2 SO4 and Na2 SO4 electrolyte as well as corresponding composites in Na2 SO4 electrolyte were tested by cyclic voltammetry, galvanostatic charge–discharge techniques and electrochemical impedance spectroscopy. It is found that compared with pure PANi prepared without PDA isomers, the incorporation of o–PDA and p–PDA is helpful to improve the electrochemical property of PANi nanofibers. Especially for o–PDA, the resulting PANi nanofibers exhibited the largest specific capacitance of 1115.7 F g −1 at the scan rate of 5 mV s −1, and 345.3 F g −1 at the specific current of 0.5 A g −1 in 1.0 M H2 SO4 electrolyte. However, in 0.5 M Na2 SO4 electrolyte, its specific capacitance decreased to 254.5 and 210.4 F g −1, whereas 834.6 and 652.5 F g −1 for PANi/PPy composites at the scan rate of 5 mV s −1 and at the specific current of 0.5 A g −1, respectively. Moreover, a great improvement on cycling stability for the composites could be achieved, benefiting from the unique core–shell nanostructure and strong synergy effect between PANi and PPy.